ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) TERHADAP LAPORAN KEUANGAN PADA USAHA KECIL MENENGAH BAHAGA MANADO - Suwintari, Ni Gusti Ayu Kade; Kalangi, Lintje; Wangkar, Anneke (Universitas Sam Ratulangi, 2018)
Small and medium enterprises (SMEs) are productive economic enterprises owned by individuals or business entities. Business activities undertaken by small and medium enterprises require a financial statement that reflects the business activities undertaken during one period. The financial statements are a form of corporate management accountability by management to external and internal parties. Seeing the importance of usability, the financial statements should be structured according to the applicable standards in order to be interpreted with the same concept and understanding by its users. The generally accepted Financial Accounting Standards make it difficult for small and medium enterprises (SMEs) who only have minimal accounting knowledge in preparing financial statements. The Financial Accounting Standards Entity Without Public Accountability (SAK ETAP) comes with the aim to accommodate the needs of entities that have no significant public accountability in the conduct of their business such as SMEs. The purpose of this study is to determine the application of Financial Accounting Standards Entity Without Public Accountability (SAK ETAP) Against Manado Financial Report. This research uses descriptive-comparative research type. The results show that Manado Manado has not fully implemented the Financial Accounting Standards of Non-Accountable Public Entity (SAK ETAP) in its financial statements. This is because the financial manpower of Manado Manado does not have sufficient knowledge about the Financial Accounting Standards of Non-Public Accountable Entity (SAK ETAP) so that it becomes a factor that Manado Bahaga has not fully implemented SAK ETAP. Instead, the company employs a competent financial personnel in their field so that they can produce financial statements in accordance with SAK ETAP.Keywords: SAK ETAP, Financial Statements, SMEs